Photos of Old Watkins Family Collage Photographs - Watkins, Howard::::::::: (1988)
Albert Watkins holding two fish he caught; standing in front of home at 207 Geneva Street, Huntington Beach Albert Watkins Plumbing sign sitting on roof over front doorway